Dialogue with Cultural Tradition: Contextualizing Fear in Lyudmila Ulitskaya’s Novel The Big Green Tent - Szabó, Tünde (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2023)
Lyudmila Ulitskaya’s works are characterized by the large number of references to the most diverse cultural phenomena of the depicted era. Her novel The Big Green Tent is dedicated to the generation ofthe dissidents of the 1960s, including their role in the cultural life of the era of the “thaw” and the “stagnation”. L. Ulitskaya evaluates the activity of this generation precisely because they “were the ﬁrst generation in Russia to overcome the fear of power”. Therefore, one of the most important components of the plot is the problem of “initiation by fear” and the possibility of overcoming it. This article considers the contextualisation of fear, the cultural and literary background, on the basis of which the fear of the heroes is comprehended. Based on the Hungarian philosopher Ágnes Heller’s concept of emotion, fear is perceived to be acomprehensive concept, combining three diﬀerent types of feelings – aﬀective, cognitive-situational and, thirdly, when the feeling becomes apersonality trait. Corresponding to these types, the contextualization of fear in the novel takes place on three levels. First, in speciﬁc situations ofthe depicted world, where the hero’s fear manifests itself as an “animal” feeling and the emphasis is placed on overcoming it. Second, fear is the subject of the hero’s reﬂections and meditations, in which its literary context is created. Third, on the author’s level, thanks to various intertextual links, the very image of the hero acquires symbolic signiﬁcance. Thus the contextualization of fear activates awide range ofcultural traditions, with which Ulitskaya’s novel enters into afruitful dialogue.